Understanding Rural Buying Behaviour: A Study with Special Reference to FMCG Products - Prakash, Gyan; Pathak, Pramod (Indian Journal of Marketing, 2014)
Rural India has become a massive consumer goods market with more than six hundred thousand villages and more than 70% of the population living in villages. In these rural markets, FMCG products have emerged as a major product category. Various researchers have found that rural and urban Indian consumers have different needs and wants. These differences have revealed a huge marketing potential for MNCs and other foreign investors, who try to explore rural regions for marketing opportunities. Thus, understanding rural consumer behaviour is very important for the marketers. This paper focused on the important factors that affect the rural purchase behaviour of FMCG products. The findings of this study indicate that price, brand name, quality, availability, packaging, and so forth were the important factors influencing the rural consumers' purchase decisions. The study also focused on the important aspects such as the effective modes of communication, reasons for switching brands, billing patterns, and satisfaction level among the rural consumers.